Daily Cannabis Use Is a Barrier to Tobacco Cessation Among Tobacco Quitline Callers at 7-Month Follow-up. Issue 10 (13th April 2022) - Goodwin, Renee D; Shevorykin, Alina; Carl, Ellen; Budney, Alan J; Rivard, Cheryl; Wu, Melody; McClure, Erin A; Hyland, Andrew; Sheffer, Christine E
Abstract: Introduction: Cannabis use is increasing among cigarette smokers in the United States. Prior studies suggest that cannabis use may be a barrier to smoking cessation. Yet, the extent to which this is the case among adults seeking to quit tobacco use remains unclear. Tobacco quitlines are the most common provider of no-cost treatment for adults who use smoke in the United States. This study investigated the association between cannabis use and smoking cessation outcomes among quitline callers. Aims and Methods: Participants included callers to the New York State Smokers' Quitline, who were seeking to quit smoking cigarettes and were contacted for outcome assessment 7 months after intake. Thirty-day point prevalence abstinence rates were calculated and compared among cannabis use groups, based on frequency of past-30-day cannabis use at baseline (none: 0 days, occasional: 1–9 days, regular: 10–19 days, and daily: 20–30 days). Results: Approximately 8.3% ( n = 283) of participants ( n = 3396) reported past-30-day cannabis use at baseline. Callers with daily cannabis use (20–30 days per month) had significantly lower odds of 30-day abstinence, relative to those who did not use cannabis (odds ratio = 0.5; 95% confidence interval [0.3, 0.9]). Conclusions: Daily cannabis use appears to be associated with poorer smoking cessation treatment outcomes among adults seeking to quit smoking cigarettes via a quitline. Because quitlines are among the most accessible, affordable, and frequently utilized community-based treatments available in the United States, and the prevalence of cannabis use is increasing among cigarette smokers, detailed inquiry into cannabis use might enhance cigarette smoking cessation outcomes. Implications: Quitlines are free of cost and accessible to millions of smokers in the United States. The current study found an inverse relationship between daily cannabis use at baseline and 30-day abstinence from cigarette smoking at 7-month follow-up among New York State Smokers' Quitline callers. Findings suggest that daily cannabis use may be a barrier to smoking cessation and sustained abstinence among those seeking help to stop smoking cigarettes.